Interaction of Opioids with TLR4—Mechanisms and Ramifications - Mai Mahmoud Gabr (MDPI AG, 2021)
The innate immune receptor toll-like receptor 4 (TLR4) is known as a sensor for the gram-negative bacterial cell wall component lipopolysaccharide (LPS). TLR4 activation leads to a strong pro-inflammatory response in macrophages; however, it is also recognised to play a key role in cancer. Recent studies of the opioid receptor (OR)-independent actions of opioids have identified that TLR4 can respond to opioids. Opioids are reported to weakly activate TLR4, but to significantly inhibit LPS-induced TLR4 activation. The action of opioids at TLR4 is suggested to be non-stereoselective, this is because OR-inactive (+)-isomers of opioids have been shown to activate or to inhibit TLR4 signalling, although there is some controversy in the literature. While some opioids can bind to the lipopolysaccharide (LPS)-binding cleft of the Myeloid Differentiation factor 2 (MD-2) co-receptor, pharmacological characterisation of the inhibition of opioids on LPS activation of TLR4 indicates a noncompetitive mechanism. In addition to a direct interaction at the receptor, opioids affect NF-κB activation downstream of both TLR4 and opioid receptors and modulate TLR4 expression, leading to a range of in vivo outcomes. Here, we review the literature reporting the activity of opioids at TLR4, its proposed mechanism(s), and the complex functional consequences of this interaction.